Interpolative Ciric-Reich-Rus Type Contractions in b-Metric Spaces: M. Pitchaimani, K. Saravanan - Team, Support (Thai Journal of Mathematics, 2021)
In this paper, we analyze the notion of interpolative Ciric-Reich-Rus type contractions in b-metric spaces to identify the fixed point and attempts to prove certain fixed point results under such mappings. In addition to this the manuscript also has an illustration to substantiate the results achieved.